Розвиток ПП «Центр безпеки «Гарант» шляхом цифрової диверсифікації напрямів діяльності - Березовський, Юрій Володимирович; Berezovskyi, Yurii Volodymyrovych (Національний університет "Львівська політехніка", 2024)
Березовський Ю.В., Шайда О.Є. (керівник). Розвиток ПП «Центр безпеки «Гарант» шляхом цифрової диверсифікації напрямів діяльності. Бакалаврська кваліфікаційна робота. – Національний університет «Львівська політехніка», Львів, 2025. Розширена анотація. У роботі досліджено теоретичні основи, нормативно-правові засади та практичні можливості цифрової диверсифікації як інструменту стратегічного розвитку суб’єктів підприємництва у сфері охоронних послуг. Зосереджено увагу на потенціалі інформаційно-комунікаційних технологій у процесі формування нових напрямів діяльності охоронного підприємства в умовах цифрової трансформації економіки [1-4]. Об’єктом дослідження виступає приватне підприємство «Центр безпеки «Гарант», яке функціонує на ринку фізичної охорони, технічного моніторингу та супровідних безпекових рішень. Предмет дослідження – система управлінських рішень щодо цифрової диверсифікації як чинника конкурентної стійкості підприємства. Метою дослідження – теоретичне обґрунтування та практичне розроблення рішень щодо цифрової диверсифікації діяльності охоронного підприємства, що дозволяють підвищити ефективність бізнес-процесів. У першому розділі висвітлено економічну сутність цифрової диверсифікації, її місце у сучасних трансформаційних процесах та роль у підвищенні економічної безпеки підприємств. Окрему увагу приділено методичним підходам до оцінювання ефективності диверсифікаційних стратегій з урахуванням цифрових індикаторів. У другому розділі проведено організаційно-економічну діагностику ПП «Центр безпеки «Гарант», що охоплює аналіз фінансового стану, структури послуг, ринкового середовища та наявних управлінських підходів. Встановлено, що підприємство має потенціал до інноваційного зростання, однак потребує розширення спектру послуг, особливо у цифровій площині. У третьому розділі запропоновано стратегічну модель цифрової диверсифікації з трьома сценаріями реалізації (базовий, інтенсивний, інноваційний), кожен з яких охоплює перелік цифрових сервісів, необхідні інвестиції, прогнозовані результати та терміни окупності.трансформація, ефективність, стратегічний розвиток, економічна безпека.

Berezovskyi Y.V., Shaida O.Ye. (Supervisor). Development of Garant Security Center PE by digital diversification of its activities. Bachelor’s Qualification Thesis. – Lviv Polytechnic National University, Lviv, 2025. Extended abstract he thesis explores the theoretical foundations, legal framework, and practical opportunities for digital diversification as a strategic development tool for enterprises in the private security sector. The focus is placed on the potential of information and communication technologies (ICT) in shaping new business lines of a security company under the conditions of digital economic transformation [1-4]. The object of the research is the private enterprise “Garant Security Center,” which operates in the market of physical security, technical surveillance, and related safety services. The subject of the research is the system of managerial decisions related to digital diversification as a factor of the enterprise’s competitive sustainability. The aim of the research is to theoretically substantiate and practically develop decisions for digital diversification of a security company’s activities, aiming to improve the efficiency of business processes. The first chapter presents the economic essence of digital diversification, its place in modern transformational processes, and its role in enhancing the economic security of enterprises. Special attention is paid to methodological approaches to evaluating the effectiveness of diversification strategies using digital indicators. The second chapter contains an organizational and economic diagnostic of PE “Garant Security Center,” covering an analysis of its financial condition, service structure, market environment, and existing managerial practices. It was established that the enterprise has potential for innovative growth but requires expansion of its service portfolio, particularly in the digital domain. The third chapter proposes a strategic model of digital diversification comprising three implementation scenarios: baseline, intensive, and innovative. Each scenario outlines a set of digital services, required investments, projected outcomes, and payback periods.
Development of Garant Security Center PE by digital diversification of its activities
Keywords: 6.076.00.00; цифрова диверсифікація; охоронні послуги; цифрова; digital diversification; security services; digital transformation; efficiency; strategic development; economic security. 1.Zhadko; K.; & Samoilenko; D. M. (2020). Economic security of enterprises in the conditions of digital technologies and pandemic. Central Ukrainian Scientific Bulletin. Economic Sciences; (5)38; 170–176. https://doi.org/10.32515/2663 1636.2020.5(38).170-176 2.Basiurkina; N.; Sedikova; I.; & Momot; K. (2022). Theoretical foundations of diversification of enterprise activities in conditions of economic instability. Ukrainian Journal of Applied Economics and Technology; 2; 54. https://doi.org/10.36887/2415 8453-2022-2-54 3.Polupanova; K.; Khadzhynova; O.; & Simanaviciene; Z. (2022). Influence of digital transformation on economic security of enterprises. Public Security and Public Order; 31; Article 17. https://doi.org/10.13165/pspo-22-31-17 4.Dergalyuk; B. (2023). Impact of digital transformation on ensuring the economic security of the enterprise. Economic Bulletin of National Technical University of Ukraine “Kyiv Polytechnic Institute”; 26; Article 10. https://doi.org/10.32782/2307-5651.26.2023.10